Doppler radar observations of an asymmetric MCS and associated vortex couplet - Scott, James D., author (Colorado State University. Libraries, 1994)
A study of the 28 May 1985 "asymmetric" mesoscale convective system (MCS) observed during PRE-STORM (Preliminary Regional Experiment for Storm scale Operational and Research Meteorology) is presented. Radar documented the evolution of this MCS from a linear squall line, to asymmetric MCS with a trailing stratiform region, to an asymmetric MCS. Before the transition to the asymmetric stage, shallow, counterrotating circulations were observed below the melting level in the trailing stratiform region of the system. With time, the anticyclonic circulation in the southern portion of the stratiform cloud began to weaken and migrate toward the convective line, while the northern, cyclonic circulation rapidly intensified, creating a asymmetric precipitation pattern. At maximum extent, the closed cyclonic circulation had horizontal dimensions of 80 km and a depth of 7 km. Retrieved horizontal pressure perturbations depict a pressure minimum in the center of the cyclonic circulation, suggesting the presence of quasibalanced flow within the vortex. A strong and deep rear inflow jet was closely linked to the amplification and maintenance of the cyclonic vortex. A similar sequence of mesoscale flow evolution has been documented in recent modeling studies.
October 1994.
Also issued as author's thesis (M.S.) -- Colorado State University, 566.
Keywords: Doppler radar; Convection (Meteorology); Radar meteorology